Grid-forming Control for Power Converters Based on Hybrid Energy Storage Systems During Islanding Operation - Nguyen, H. V.; Trinh, C. T.; Vu, G. H.; Bui, H. V.; Nguyen, M. D.; Nguyen, S. H.; Quach, C. D.; Hoang, N. T. (Radioengineering society, 2024)
Energy storage systems are increasingly playing a pivotal role in power systems. The combination of distributed sources and energy storage systems with local loads forms an autonomous distribution grid (ADG) capable of flexibly operating in either islanding or grid-connected modes. It is essential to maintain the state variables of the grid, such as frequency and voltage, within permitted ranges during islanding mode, where the power converter control plays the most important role in the system operation. This paper proposes a control method for the power converter associated with a hybrid energy storage system (ESS) that is capable of forming the distribution grid during the islanding mode as well as following to the grid in grid-connected mode. The control method is based on a centralized energy controller to distribute energy between a battery and a supercapacitor. Accordingly, two voltage and current control loops using a PI hybrid fuzzy controller are designed. Simulation is developed using Matlab/Simulink software for a case study of a distribution network to illustrate the efficiency of the proposed control method.
Keywords: Converters; energy storage systems; power distribution networks; supercapacitors